High-Value Plant Species Used for the Treatment of "Fever" by the Karen Hill Tribe People - Methee Phumthum; Nicholas J. Sadgrove (MDPI AG, 2020)
The symptom "fever" is generally not itself a terminal condition. However, it does occur with common mild to severe ailments afflicting the world population. Several allopathic medicines are available to attenuate fever by targeting the pathogen or the symptom itself. However, many people in marginal civilizations are obligated to use locally grown medicinal plants due to limited access to common pharmaceuticals. The Karen ethnic group is the biggest ethnic minority group in the hill-tribes of Thailand. They utilise a vast repertoire of medicinal plant species. Since many modern drugs were discovered out of traditional therapies, it is possible to discover new allopathic drugs in the treatment of fever and associated pathogens from the Karen people. Thus, this study aims to identify and record the ethnomedicinal plants they used for the treatment of "fever". The names of plants used by the Thai Karen people for the treatment of fever were mined from publications on ethnomedicinal uses. Useful plant species and families were identified using the Cultural Importance Index (CI). With the mined data, 125 plant species from 52 families were identified, distributed across 25 Karen villages. A chemical cross-examination of these species provided valuable insights into chemical classes worthy of further investigation in the context of fever and associated pathogens.